A nonmonotone smoothing Newton algorithm for solving general box constrained variational inequalities. (3rd August 2018) - Zhao, Na; Ni, Tie
Abstract: In this paper, based on a new smoothing function, the general box constrained variational inequalities are solved by a smoothing Newton algorithm with a nonmonotone line search. The proposed algorithm is proved to be globally and locally superlinearly convergent under suitable assumptions. The preliminary numerical results are reported.